C61 MULTIDISCIPLINARY MANAGEMENT IN A CASE OF EOSINOPHILIC MYOCARDITIS WITH CHURG STRAUSS SYNDROME: FROM ECG TO ENDOMYOCARDIAL BIOPSY. (18th May 2022) - Amelotti, N; Mapelli, M; Pires, I; Guglielmo, M; Majocchi, B; Catto, V; Campodonico, J; Vignati, C; Baggiano, A; Ribatti, V; Moltrasio, M; Vettor, G; et al.
Abstract: Background: Eosinophilic granulomatosis with polyangiitis (EGPA), previously known as Churg–Strauss, is a rare multisystem disorder characterized by chronic rhinosinusitis, asthma, and prominent peripheral blood eosinophilia (PE). Cardiac involvement may include eosinophilic myocarditis and it is a serious manifestation of EGPA. Case Presentation: A 67–year–old woman presented to the emergency department with 2–weeks history of dyspnea, orthopnea and asthenia. She had history of asthma, PE, adjuvant radiotherapy after right mastectomy (July 2021). The patient was diagnosed with new onset atrial fibrillation in the previous month. At admission, the patient was hemodynamically stable and with signs of congestion. Complementary exams showed sinus rhythm and T–wave inversion on lateral leads; PE (2010/uL), elevated troponin and BNP values; and severe biventricular systolic dysfunction with diffuse hypokinesia and apical akinesia. The patient was admitted to the ICU and was treated with intravenous diuretics and levosimendan. Optimal HF therapy was introduced. Serial echocardiography revealed partial recovery of LVEF and blood analysis showed a decrease in troponin levels, with persistent eosinophilia (6330/uL). Computed tomography (CT) excluded significant coronary disease, and showed bilateral basal ground–glass opacities, areas of air–space consolidation and bilateral reticular–nodular pattern. Cardiac magnetic resonance revealed increased T2 values/signs of myocardial edema in anterior wall, interventricular septum and apex and no late gadolinium enhancement, compatible with myocarditis. An endomyocardial biopsy (EMB) was performed and confirmed the diagnosis of eosinophilic myocarditis. Oral corticosteroids were started. Paranasal CT scan showed signs of chronic sinusitis, without polyposis, and antineutrophil cytoplasmic antibodies were positive, making the diagnosis of EGPA, according to ACR criteria. Discussion: In a patient presenting with new onset heart failure and with history of asthma and eosinophilia, it is important to suspect eosinophilic myocarditis, as this is a rare but reversible life–threatening condition. EMB plays an important role in the diagnosis and should be done promptly. Conclusion: We described a multidisciplinary management of a case of a patient with eosinophilic myocarditis and EGPA, presenting with severe acute biventricular dysfunction.